2019
DOI: 10.14254/2071-8330.2019/12-2/11
|View full text |Cite
|
Sign up to set email alerts
|

Globalization of the labour market – Circular migration in Hungary

Abstract: Explanation of the recently intensified willingness to migrate has many components, among which migration for the purpose of employment is a paramount one. The study deals with the exploration of the three basic characteristics of globalizing employment in Central and Eastern Europe and Hungary in particular: migration motivations of foreign employees, their labour market characteristics and the degree of their social integration. The authors aim to provide a comprehensive picture of the content of engagement-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Results were the followings: 0.76 percent means that language is almost deterministic for labour migration. The evidence was supported by Cseh-Papp et al (2018). They found that the absolute majority of migrants chose foreign employment because of "family reasons" (38 percent) or "personal reasons" (20 percent), while "economic reasons" were marked the most rarely.…”
Section: Pillars Of Migrationmentioning
confidence: 91%
See 4 more Smart Citations
“…Results were the followings: 0.76 percent means that language is almost deterministic for labour migration. The evidence was supported by Cseh-Papp et al (2018). They found that the absolute majority of migrants chose foreign employment because of "family reasons" (38 percent) or "personal reasons" (20 percent), while "economic reasons" were marked the most rarely.…”
Section: Pillars Of Migrationmentioning
confidence: 91%
“…However, once it got noted that this break line has weak explanatory ability, researchers' interest swayed toward linguistic, ethnic, cultural and psychological characteristics (Schiffauer & Schiaffauer, 2017;Bodó, 2016) as well as toward the demographic features of the country and particularly its emigrant population (Streimikiene et al, 2016). The chance for successful identification (emotional integration) of foreigners correlates to their level of interest toward the host country's customs and traditions (Cseh-Papp et al, 2018). It was already indicated above that ethnical background and cultural proximity do count, as countries attempt to lure back their fellows (Hungary-Romania).…”
Section: Literature Reviewmentioning
confidence: 96%
See 3 more Smart Citations